Feed wafers from fermented sugarcane tops and Tithonia diversifolia with added tapioca starch: Effects on physical quality and in-vitro parameters for ruminant feed - Novirman Jamarun; Zaitul Ikhlas; Mardiati Zain; Windu Negara; Roni Pazla; Gusri Yanti (Open Veterinary Journal)
Background: Alternative feeds for ruminants that can be explored are sugarcane tops as a source of crude fibre and tithonia as a source of protein. Long droughts and direct use of these components may not meet nutritional standards. Processing technologies such as wafer production, using tapioca starch as an adhesive, can improve feed durability, storage and nutritional consistency. The addition of tapioca starch in ruminants feed should be considered, as its high starch content may affect overall feed digestibility.